Composite adsorption material applied to CO2 gas-liquid separation and preparation method thereof
By using gradient carbonized pine wood powder and modified zeolite composite materials, the problems of adsorption capacity decay and high energy consumption regeneration in CO2 heat pump systems under high humidity have been solved, achieving efficient CO2 adsorption, VOCs removal and wastewater purification, and adapting to various chemical scenarios.
Patent Information
- Application Number
- CN202511642584.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-11
- Publication Date
- 2026-01-23
AI Technical Summary
In existing CO2 heat pump systems, zeolite and biomass carbon materials suffer severe CO2 adsorption capacity decay under high humidity conditions, and cannot simultaneously meet the multiple requirements of gas-liquid separation, wastewater treatment, and exhaust gas purification, resulting in problems such as microbial growth and high-energy-consumption regeneration.
By using directional carbonized pine wood powder and modified zeolite composite materials, a multi-layer structure is formed through gradient carbonization, rare earth modification, nanoparticle photocatalysis, and hydrophobic modification, achieving high moisture resistance, low energy consumption regeneration, and broad-spectrum antibacterial effect.
Under high humidity conditions, the CO2 adsorption capacity decays little, energy consumption is reduced by 40%, and regeneration efficiency is increased by 50%. It has the functions of CO2 adsorption, VOCs removal and wastewater purification, and is suitable for a variety of chemical industry scenarios.
Smart Images

Figure 1C33381C-1AC4-478A-BA28-83FF93BB5471 
Figure 52E09D03-FCA7-4D0B-81DE-FF6004DB26D3 
Figure 67943BA9-9DA6-4DAD-9510-4A19E7953BCC
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of chemical material preparation, and particularly relates to a CO2 heat pump system, in particular to a composite adsorption material applied to CO2 gas-liquid separation and a preparation method thereof. BACKGROUND
[0002] In a transcritical CO2 heat pump system, the gas-liquid separation efficiency directly affects the system energy efficiency, and in the prior art, zeolite and / or biomass carbon are mostly used, wherein the zeolite has strong selectivity for CO2 adsorption, but is brittle and has poor formability, and the biomass carbon has a porous structure and low cost advantages, but its surface function is single, the nucleophilicity for CO2 is insufficient, and the adsorption amount is small. Therefore, the materials selected in the prior art are compounded and modified.
[0003] In the existing patent CN117101603A, the zeolite-biomass carbon adsorbent is synthesized by one-step synthesis, and the interface bonding problem of the biomass carbon and the zeolite is not solved, which leads to component peeling in the recycling use, the CO2 capacity attenuation is more than 30% under the CO2 heat pump working condition of relative humidity greater than or equal to 80%, and the capacity is only 18 mg / g under 90% humidity; the single formula of the zeolite-biomass carbon adsorbent cannot meet the different requirements of low-temperature adsorption required by the heat pump gas-liquid separation, hydrophilicity required by waste water treatment, and hydrophobicity required by waste gas purification, and microorganisms are easy to breed in long-term use.
[0004] Although some researches improve the adsorption performance through nanoparticle modification, the specific performance improvement effect is not clear, and practical application has not been seen. Therefore, people urgently need a technical solution to solve the above problems. SUMMARY
[0005] In order to solve the problems of the prior art, the application provides a composite adsorption material applied to CO2 gas-liquid separation and a preparation method thereof, which has the effects of high moisture resistance, low energy consumption regeneration, and broad-spectrum antibacterial effect.
[0006] The technical problem to be solved by the application is solved by the following technical scheme: A composite adsorption material applied to CO2 gas-liquid separation, raw materials include, by weight: 20-35 parts of directional carbonized pine powder, 45-60 parts of 13X / NaY type zeolite, 2-4 parts of rare earth modifier, 1-3 parts of nano functional particles, 0.5-2 parts of hydrophobic modifier, 5-10 parts of inorganic binder, and 0.5-1.5 parts of low-temperature sintering aid.
[0007] The directional carbonized pine powder is carbonized at 500-550 DEG C in stages, and the specific surface area is greater than or equal to 400 m 2 / g; The zeolite is compounded by 13X type and NaY type in a weight ratio of 0-1:1-0. The nano functional particles are TiO2 or ZnO, and the particle size is 20-50 nm; The rare earth modifier is a salt solution of La 3+ ion or Ce 3+ ion; The hydrophobic modifier is KH-570; The inorganic binder is a mixture of silica sol and aluminum sol at a weight ratio of 1:1; The low-temperature sintering aid is Li2O3, and the sintering temperature is controlled at 250-280 DEG C.
[0008] Based on the above raw materials, the preparation method of the composite adsorption material for CO2 gas-liquid separation includes the following steps: (1) The pine powder is acid washed and gradient carbonized at 500-550 DEG C to obtain directional carbonized pine powder; (2) The zeolite and the rare earth modifier are stirred at 65 DEG C for 3 h, and the nano functional particles are ultrasonically dispersed to obtain a double modified zeolite; (3) The directional carbonized pine powder, the double modified zeolite, the inorganic binder and the low-temperature sintering aid are mixed, and the hydrophobic modifier is coated in situ by spraying, and then double screw extrusion is performed; (4) 250-280 DEG C continuous sintering, to obtain a composite adsorption material.
[0009] The gradient carbonization of the pine powder is carried out under a nitrogen atmosphere with continuous heating, and the heating stage includes 200 DEG C for 1 h, 400 DEG C for 1 h and 550 DEG C for 1 h, and the temperature is slowly raised at 5 DEG C / min.
[0010] The mixing of the zeolite and the rare earth modifier solution is mixed according to a solid-liquid ratio of 1:8.
[0011] In the present application, the application of the composite adsorption material for CO2 gas-liquid separation includes: (1) Adjust the formula according to the application scene: add 1-1.2 parts by weight of the hydrophobic modifier in the heat pump scene, and remove the hydrophobic modifier in the water treatment scene; (2) When the adsorption capacity decreases to 80% of the initial value, regenerate the composite adsorption material.
[0012] The regeneration includes: (1) Photocatalysis: first start the ultraviolet light, and use the photocatalysis of TiO2 in the material under ultraviolet light (wavelength 254 nm) to decompose the adsorbed organic pollutants (VOCs, etc.), and shorten the time to 2 h compared with the traditional regeneration; (2) Low-temperature hot air cooperation: after 20-30 min of photocatalysis operation, the hot air is started synchronously, 40 DEG C hot air is used, and the wind speed is 0.5-1 m / s, which assists in desorbing the physically adsorbed CO2 and water vapor; (3) Regeneration termination: when the CO2 concentration in the outlet gas is reduced to the ambient concentration (about 0.04%), the ultraviolet light is turned off, and the hot air is turned off after 10 min, and the material adsorption capacity is restored to more than 95% of the initial value.
[0013] In the present application, a three-layer structure of "directional carbonized pine support skeleton + rare earth / nanoparticle double-modified zeolite adsorption core + hydrophobic coating protective layer" is adopted, and each layer forms a synergistic effect through molecular and interface interactions.
[0014] The directional carbonized pine provides a gradient porous support structure, which is the result of the carbonization evolution law of wood cell walls and the phased temperature control strategy: (1) Gradient pore formation principle: pine raw materials contain 40-50% cellulose, 20-30% hemicellulose, and 20-30% lignin. When the temperature is raised in stages in a nitrogen atmosphere: 200℃ stage: only free water and bound water in wood are removed, and the cell wall structure is intact, providing a template for subsequent pore formation; 400℃ stage: hemicellulose is completely decomposed into small molecule volatile components such as acetic acid and furans, forming micropores with a diameter of 2-5 nm in the cell wall, which are suitable for CO2 molecule diffusion, and the CO2 molecule kinetic diameter is about 0.33 nm; 550℃ stage: lignin is gradually carbonized to form mesopores with a diameter of 20-50 nm, reducing the overall density of the material, and serving as an anchoring site for zeolite particles; Finally, a gradient distribution of micropores and mesopores is formed, which not only ensures the rapid diffusion channel of CO2, but also reduces the bulk density of the material through the mesopore structure, avoiding the structural composite problem of the heat pump separation device due to excessive material weight.
[0015] (2) Structure stability principle: the inert protection of nitrogen atmosphere can prevent oxidation and combustion during the carbonization of wood, which would cause pore collapse. The graphite-like structure formed after the carbonization of lignin can improve the compressive strength of the support skeleton by 348 kJ / mol of C-C bond energy, solving the defect of brittle and easy breakage of pure carbonized pine, and adapting to the filling and long-term operation requirements of industrial devices.
[0016] Zeolite is the adsorption core carrier, which is modified by rare earth ions and nanoparticles to realize the functions of CO2 selective adsorption, low energy consumption regeneration, and antibacterial properties.
[0017] (1) Rare earth modification enhances CO2 adsorption performance based on coordination adsorption and electronic effect regulation. Rare earth ions interact with zeolite through ion exchange and surface loading: Ion exchange: 13X / NaY type zeolite has a three-dimensional pore structure with a pore size of 0.7-0.8 nm. Na+ (Ionic radius 0.095 nm) can react with La 3+ (Ionic radius 0.103 nm), Ce 3+ (Ionic radius 0.101 nm) An exchange occurs, and the exchanged rare earth ions serve as active adsorption sites. As a polar molecule with a dipole moment of 0.11 D, the O atom of CO2 can form coordinate bonds with rare earth ions, with bond energies of approximately 80-100 kJ / mol. This synergistic effect of chemisorption and physisorption significantly enhances the adsorption selectivity of CO2. Compared to water vapor, which has an interaction energy of approximately 40-50 kJ / mol with rare earth ions, CO2 preferentially occupies active sites in competitive adsorption, thus maintaining low attenuation even at 90% high humidity.
[0018] Low-temperature adsorption enhancement principle: Rare earth modification can reduce the adsorption enthalpy change of CO2 by zeolite from -35 kL / mol to -28~-30 kJ / mol of pure zeolite. According to the adsorption thermodynamic formula ΔG=ΔH-TΔS, the lower adsorption enthalpy change means that CO2 molecules can still overcome diffusion resistance and be adsorbed in low-temperature environments such as heat pumps operating at -10℃, thus avoiding the phenomenon of a sudden drop in the low-temperature adsorption capacity of pure zeolite.
[0019] (2) TiO2 / ZnO nanoparticles achieve low-energy regeneration and antibacterial effects through photocatalytic oxidation and slow release of metal ions: Photocatalytic regeneration: TiO2 is a wide bandgap semiconductor with a bandgap of 3.2 eV. Under ultraviolet light irradiation at a wavelength of 254 nm, valence band electrons are excited to the conduction band, forming electron-hole pairs (e-hole pairs). - -h + ), hole (h + It possesses strong oxidizing properties, with an oxidation potential of 2.7 eV. It can react with H2O adsorbed on the material surface to generate hydroxyl radicals (·OH), with an oxidation potential of 2.8 eV. ·OH can non-selectively decompose adsorbed VOCs, such as toluene and xylene, into CO2; simultaneously, electrons (e... - It can react with O2 to generate superoxide anion·O2. - This further enhances the degradation of organic pollutants. This photocatalytic decomposition replaces the traditional high-temperature thermal desorption, reducing the regeneration temperature from 120-150 ℃ to 40 ℃. Only low-temperature hot air is needed to assist in the desorption of physically adsorbed CO2, reducing regeneration energy consumption by 40%.
[0020] Spectral antibacterial effect: ·OH and ·O2 generated during TiO2 photocatalysis - It can damage the cell membranes of microorganisms, degrade DNA and proteins, leading to microbial inactivation; ZnO, on the other hand, slowly releases Zn. 2+ Zn 2+It can be combined with the thiol-SH of microorganisms, inhibit enzyme activity, block metabolic process, both synergistically inhibit bacteria rate ≥ 99.5%, solve the problem of microbial breeding in high humidity environment of heat pump, and further block the hole.
[0021] (3) The hydrophobic modifier KH-570 forms a protective layer by interfacial grafting, and the principle is based on the molecular design of silane coupling agent: The KH-570 molecule contains a siloxane group -Si(OCH3)3 and a hydrophobic organic group -C(CH3)=CH2. The siloxane group can hydrolyze and condense with the hydroxyl group -OH on the surface of zeolite / carbonized pine, forming a Si-O-C covalent bond, realizing molecular level grafting, and the hydrophobic organic group forms a dense layer of methyl on the material surface, so that the contact angle of the material surface is increased from hydrophilic 30° of pure zeolite to hydrophobic 105°-110°.
[0022] Anti-high humidity and adsorption balance: the hydrophobic coating only acts on the outer surface of the material and the inner wall of the large pore, does not block the 2-5 nm micropore required for CO2 diffusion, and the water vapor is difficult to condense on the material surface due to the difference in surface energy, reducing the problem of water vapor occupying the adsorption site. At the same time, CO2 molecules can penetrate the hydrophobic layer and quickly diffuse to the adsorption core due to the strong interaction between the polarity and the rare earth active site, realizing the balance of anti-high humidity and high adsorption capacity.
[0023] In the present application, the four-step continuous process of pine gradient carbonization, zeolite double modification, in-situ coating forming and continuous sintering solves the problems of uneven dispersion of biomass-inorganic composite system components, weak interface bonding and poor batch stability.
[0024] (1) The traditional one-step high-temperature carbonization process is easy to cause wood explosion, and the volatile matter is quickly released to break the cell wall. The present application adopts staged temperature control: The thermal decomposition activation energy of hemicellulose is about 120 kJ / mol, which is lower than that of lignin about 180 kJ / mol. The hemicellulose can be completely decomposed by keeping at 400℃ for 1h, avoiding the secondary pore forming caused by the residual hemicellulose in the subsequent carbonization. Keeping at 550℃ for 2h can make lignin gradually carbonize (lignin carbonization is divided into three stages: 350-450℃ preliminary decomposition, 450-550℃ deep carbonization, and above 550℃ graphitization). By slowly increasing the temperature at 5℃ / min, the volatile release rate is controlled to be ≤0.5 g / min·kg, avoiding the collapse of the pore, and finally ensuring that the specific surface area of carbonized pine is ≥400 m 2 / g, porosity is ≥70%, and batch deviation is ≤3%.
[0025] (2) Zeolite double modification is to realize uniform loading of rare earth ions and dispersion stability of nanoparticles, and its principle depends on ultrasonic cavitation effect and solid-liquid ratio regulation: When modified by rare earth, zeolite and La(NO3)3 solution can ensure that the solution fully penetrates the zeolite pore, and constant temperature stirring at 65°C can improve the ion exchange rate, so that the rare earth loading is controlled at 1.5-2 wt%, and the deviation is ≤0.1 wt%; the ultrasonic dispersion of nano TiO2 / ZnO utilizes the cavitation effect to break the agglomerates of nanoparticles, ensuring that the nanoparticles uniformly cover the zeolite surface, and the exposure rate of the photocatalytic active site is increased by 60%.
[0026] (3) In-situ coating to construct a molecular bridge interface layer: carbonized pine powder and double-modified zeolite are mixed to form a preliminary wrapping structure, after spraying KH-570, the siloxane groups of KH-570 react with the residual hydroxyl groups on the surface of pine and the hydroxyl groups on the surface of zeolite, forming covalent bond connection of pine-KH570-zeolite, and the interfacial bonding strength is increased to 1.8 MPa.
[0027] (4) Low-temperature sintering aid Li2CO3 reduces the sintering activation energy: the melting point of Li2CO3 is 723°C, but in the presence of silica sol / alumina sol, a eutectic is formed, and the melting temperature is reduced to about 240°C. The molten Li + can penetrate into the surface of inorganic binder silica sol / alumina sol and substrate, promote the formation of SiO2-Al2O3 network structure, and reduce the sintering activation energy from 200 kJ / mol of pure binder to 120 kJ / mol.
[0028] In this application, multiple scenarios are adapted by adjusting the component ratio, and the key performance of the material is targeted and controlled according to the scene requirements.
[0029] (1) The demand of CO2 heat pump gas-liquid separation scene is low temperature resistance to high humidity and high efficiency CO2 separation, therefore the principle of formula adjustment is: increase the amount of hydrophobic modifier, which can increase the surface contact angle to 110°, further reduce the water vapor adsorption under high humidity working condition; La 3+ Compared with Ce 3+ The adsorption enthalpy of CO2 is lower (La 3+ Modified adsorption enthalpy-28 kJ / mol, Ce 3+ Modified-30 kJ / mol), and the adsorption capacity is higher at-10°C low temperature (La 3+ Modified adsorption capacity 29.2 mg / g, Ce 3+ Modified 27.5 mg / g), so it is suitable for low temperature working condition of heat pump.
[0030] (2) The requirement of high-humidity VOCs purification scene is efficient photocatalysis and moisture resistance, so the principle of formula adjustment is: increasing the amount of TiO2 can improve the photocatalytic active site density, and the toluene degradation rate is increased from 85% to 91%; appropriately reducing the amount of hydrophobic modifier can reduce the surface contact angle to 100°, which can avoid excessive water vapor adsorption and provide a smoother diffusion channel for VOCs molecules, and balance the moisture resistance and VOCs adsorption.
[0031] (3) The requirement of high-salt wastewater phosphorus adsorption scene is hydrophilic adsorption and salt tolerance, so the principle of formula adjustment is: after removing the hydrophobic modifier, the material surface restores hydrophilic, the contact angle is ≤40°, which is convenient for wastewater to penetrate into the adsorption core; Ce 3+ has a stronger coordination with phosphate PO4 3- than La 3+ , the Ce-P bond energy is about 120 kJ / mol, the La-P bond energy is about 100 kJ / mol, and Ce 3+ does not easily compete with Cl - for adsorption in a high-salt environment such as 10 g / L NaCl, so the phosphate adsorption capacity is 18.5 mg / g, and the salt tolerance is excellent.
[0032] Compared with the prior art, the present application has the following advantages: (1) The product prepared by the present application has a small CO2 adsorption capacity attenuation under 90% relative humidity, which solves the problem of failure of the heat pump under high-humidity working conditions; (2) The present application can reduce the energy consumption by 40% and improve the regeneration efficiency by 50% through photocatalysis and low-temperature hot air composite regeneration compared with traditional thermal regeneration; (3) The product prepared by the present application has CO2 adsorption, VOCs removal, wastewater purification and antibacterial functions, and is suitable for various chemical scenes, so the application range is wide. BRIEF DESCRIPTION OF DRAWINGS
[0033] Figure 1 is a process flow chart of the preparation method of the present application; Figure 2 is a comparison chart of CO2 adsorption capacity of the composite adsorption material obtained by the present application under different humidities; Figure 3 is a comparison chart of regeneration energy consumption-cycle number of the composite adsorption material obtained by the present application; Figure 4 is a comparison chart of antibacterial rate-culture time of the composite adsorption material obtained by the present application. DETAILED DESCRIPTION
[0034] The present application is further described below in combination with the drawings of the specification and specific preferred embodiments, but the protection scope of the present application is not limited thereby.
[0035] Example 1 A method for preparing a composite adsorbent material for CO2 gas-liquid separation, such as Figure 1 As shown, it includes the following steps: S1: Raw Material Preparation Calculated by weight parts: 20-35 parts of directional carbonized pine wood powder, 45-60 parts of 13X / NaY type zeolite, 2-4 parts of rare earth modifier La(NO3)3 / Ce(NO3)3, 1-3 parts of nano-functional particles TiO2 / ZnO, 0.5-2 parts of hydrophobic modifier KH-570, 5-10 parts of inorganic binder silica sol / alumina sol, and 0.5-1.5 parts of low-temperature sintering aid Li2CO3.
[0036] S2: Gradient carbonization of pine wood S2-1 Raw material pretreatment: Pine wood scraps are crushed to 80-120 mesh size by a double hammer mill to obtain pine wood powder. The powder is then acid-washed with 1 mol / L H2SO4 for 30 min to remove lignin, and then washed with distilled water until neutral. S2-2 Gradient Carbonization: Pretreated pine powder is fed into a continuous tunnel carbonization kiln and subjected to five-stage temperature control under a nitrogen atmosphere: 200℃ for 1 h; heating at 5℃ / min to 400℃; holding at 400℃ for 1 h; heating at 5℃ / min to 550℃; and holding at 550℃ for 2 h. The resulting directionally carbonized pine powder has a specific surface area ≥400 m². 2 / g, porosity ≥70%; S2-3 Screening: Impurities are removed by a 300-mesh vibrating screen and the material is continuously conveyed to the mixing section.
[0037] S3: Zeolite dual modification S3-1 Rare Earth Modification: In a continuously stirred reactor, zeolite and La(NO3)3 or Ce(NO3)3 solution are mixed at a solid-liquid ratio of 1:8, and stirred at a constant temperature of 65℃ for 3 h at a speed of 300 r / min to achieve uniform loading of rare earth ions, with a loading amount of 1.5-2 wt%. S3-2 nanocomposite: Add TiO2 or ZnO nanoparticles with a particle size of 20-50 nm, ultrasonically disperse at 65℃ for 30 min, ultrasonic power 5 kW, and continuously dry at 105℃ to obtain double-modified zeolite. S3-3 Detection: Rare earth loading is monitored in real time by X-ray fluorescence spectroscopy (XRF), with deviation controlled within ±0.1 wt%.
[0038] S4: In-situ coating - continuous molding S4-1 Mixing ratio: Add directional carbonized pine wood powder, double-modified zeolite, inorganic binder, and low-temperature sintering aid to a high-speed mixer according to the weight parts, and mix for 10 min at a speed of 1500 r / min. S4-2 In-situ coating: Spray KH-570 hydrophobic modifier, mix and coat, keep temperature at 80°C to avoid volatilization of modifier, form pine-zeolite interface coating layer; S4-3 Continuous forming: extrude φ3-8 mm columnar / plate-shaped blanks through a double screw extruder at a temperature of 120-150°C, a screw speed of 80 r / min, and an extrusion pressure of 8 MPa, with the blank density controlled at 0.8-1.0 g / cm 3 .
[0039] S5: Low-temperature continuous sintering S5-1 Subsection sintering: in a mesh belt sintering furnace, first remove water at 200°C for 1 h, then sinter and solidify at 260°C for 2 h under N2 atmosphere, and then naturally cool to room temperature; S5-2 Polishing: remove surface burrs through a brush-type polishing machine to obtain finished adsorbent material; S5-3 Detection: randomly sample and test the adsorption capacity, compressive strength, and rare earth loading, with a batch stability deviation of ≤5%.
[0040] S6: Regeneration S6-1 Photocatalytic regeneration: when the material adsorption capacity decreases to 80% of the initial value, start the ultraviolet light with a power of 100-200 W without turning on the hot air; S6-2: Low-temperature hot air synergy: after 20-30 min of photocatalytic operation, simultaneously turn on the 40°C hot air, which is uniformly introduced from the bottom of the material to ensure penetration; S6-3: Synergy termination: by real-time monitoring of the outlet gas, when the CO2 concentration decreases to the ambient concentration (0.04%), first turn off the ultraviolet light, and then turn off the hot air after 10 min. The preheated desorbed residual CO2 is used to regenerate the material, and after regeneration, the material adsorption capacity is restored to more than 95% of the initial value.
[0041] Example 2 This example tests the product obtained in Example 1 to verify its functional effect.
[0042] 1. Verification of high-humidity CO2 adsorption performance 1.1 Purpose of the experiment: verify the CO2 adsorption capacity of the material in this scheme under high humidity conditions (simulating the actual operating environment of a CO2 heat pump), and compare the capacity decay problem of existing technology under high humidity.
[0043] 1.2 Experimental design: Experimental group: the core formula in this scheme 3 corresponds to different scenarios Experimental group 1: CO2 heat pump special formula: directional carbonized pine powder 30 parts, 13X zeolite 55 parts, La(NO3)3 3.5 parts, TiO2 2 parts, KH-570 1.2 parts; Experimental group 2: High humidity VOCs purification formula: directional carbonized pine powder 25 parts, NaY zeolite 60 parts, Ce(NO3)3 3 parts, TiO2 2.5 parts, KH-570 0.8 parts; Experimental group 3: High salt wastewater formula: no hydrophobic modification, directional carbonized pine powder 35 parts, 13X zeolite 45 parts, Ce(NO3)3 4 parts, ZnO 3 parts.
[0044] Control group: 2 kinds of existing technology materials Control group 1: Pure 13X zeolite, commercial grade, no modification; Control group 2: Traditional zeolite-carbonized pine composite: 13X zeolite 60 parts, unmodified carbonized pine 40 parts, no rare earth / hydrophobic modification.
[0045] Experimental conditions: temperature 25℃ (normal temperature), -10℃ (heat pump low temperature working condition), relative humidity (RH) 30% (dry), 60% (medium humidity), 90% (high humidity), CO2 concentration 10% (simulated heat pump system CO2 partial pressure), adsorption time 120 min (to ensure saturation).
[0046] Performance standard: GB / T 39753-2021.
[0047] 1.3 The experimental results are shown in Table 1: Table 1 Comparison of CO2 adsorption capacity under different humidity Group Material formula / type Experimental conditions (temperature / humidity) CO2saturated adsorption capacity (mg / g) Capacity attenuation rate Experimental group 1 Heat pump special formula 25℃ / 30%RH 32.5 - 25℃ / 90%RH 30.8 5.2% -10℃ / 30%RH 29.8 - -10℃ / 90%RH 28.2 5.4% Experimental group 2 High humidity VOCs purification formula 25℃ / 30%RH 31.2 - 25℃ / 90%RH 29.5 5.4% Experimental group 3 High salt wastewater formula 25℃ / 30%RH 28.6 - 25℃ / 90%RH 22.1 22.7% Control group 1 Pure 13X zeolite 25℃ / 30%RH 26.8 - 25℃ / 90%RH 16.1 39.9% -10℃ / 30%RH 16.1 - -10℃ / 90%RH 9.7 39.7% Control group 2 Traditional zeolite-carbonized pine 25℃ / 30%RH 22.5 - 25℃ / 90%RH 13.8 38.7% -10℃ / 30%RH 13.5 - -10℃ / 90%RH 8.2 39.3% From the above data, it can be seen that the experimental group 1 (heat pump special) of the present scheme has a capacity attenuation rate of only 5.2%-5.4% under high humidity (90% RH), which is much lower than the control group (38.7%-39.9%), verifying the anti-high humidity effect of hydrophobic + rare earth modification; Experimental group 3 has a high humidity attenuation rate of 22.7% due to no hydrophobic modification, which proves the necessity of hydrophobic modification. Figure 2 The same effect is also shown.
[0048] 2. Low energy consumption regeneration performance verification 2.1 Experimental purpose: Verify the energy consumption advantage of the photocatalysis + low temperature hot air regeneration method of the present scheme, and compare the energy consumption and efficiency of traditional high temperature heat regeneration.
[0049] 2.2 Experimental design: Experimental group: Heat pump special formula of the present scheme (experimental group 1), using two regeneration methods Experimental group 1-1: photocatalysis + 40°C low-temperature hot air (ultraviolet light wavelength 254 nm, power 100 W; hot air speed 0.5 m / s); Experimental group 1-2: only photocatalysis (no hot air, the same as 1-1).
[0050] Control group: traditional regeneration method of prior art material Control group 1-1: pure 13X zeolite (control group 1), 120°C high-temperature hot air regeneration (hot air speed 0.5 m / s); Control group 2-1: traditional zeolite-carbonized pine (control group 2), 150°C high-temperature hot air regeneration (hot air speed 0.5 m / s).
[0051] Experimental conditions: all materials are first adsorbed CO2 to saturation at 25°C / 90% RH, and then the regeneration experiment is performed, the regeneration focus is “the adsorption amount is restored to more than 90% of the initial value”, and the regeneration energy consumption (kW·h / kg material), regeneration time, capacity recovery rate are recorded.
[0052] 2.3 Experimental results are shown in Table 2: Table 2 is the regeneration energy consumption-cycle number comparison experimental data Group Material formula / regeneration method Regeneration energy consumption (kW·h / kg) Regeneration time (min) Capacity recovery rate after regeneration (%) Experimental group 1-1 Heat pump formula + photocatalysis + 40℃ hot air 3.2 60 98.5 Experimental group 1-2 Heat pump formula + only photocatalysis 2.8 120 92.3 Control group 1-1 Pure 13X zeolite + 120℃ hot air 5.3 80 95.2 Control group 2-1 Traditional composite + 150℃ hot air 6.8 100 90.1 From the above data, it can be seen that the regeneration energy consumption of experimental group 1-1 of the present scheme is 3.2 kW·h / kg, which is reduced by more than 40% compared with the control group (reduced by 40% compared with control group 1-1, reduced by 53% compared with control group 2-1), and the capacity recovery rate is 98.5%, which is higher, verifying the advantages of low-energy regeneration; the regeneration energy consumption of only photocatalysis is lower but the time is longer, which can be selected according to the actual scene. Figure 3 The same effect is also shown.
[0053] 3. Broad-spectrum bacteriostatic performance verification 3.1 Experimental purpose: verify the inhibition effect of TiO2 / ZnO nanoparticles in the present scheme on common microorganisms, and compare the bacteriostatic defects of unmodified materials 3.2 Experimental design Experimental group: the formula containing nanoparticles in the present scheme 2 Experimental group 1: special formula for heat pump (containing TiO2 2 parts); Experimental group 2: high-humidity VOCs purification formula (containing TiO2 2.5 parts); Control group: existing material without nanoparticles Control group 1: pure 13X zeolite (control group 1); Control group 2: traditional zeolite-carbonized pine composite (control group 2).
[0054] Experimental conditions: plate counting method was used, E. coli (ATCC 25922), S. aureus (ATCC 29213) were inoculated, the concentration of the bacterial solution was 10 6 CFU / mL, the amount of material was 1 g / 10 mL of bacterial solution, 25°C culture for 24 h; the mold registration test referred to GB / T 24346-2009, Aspergillus niger was inoculated and cultured for 7 days.
[0055] Execution standard: GB / T 21866-2008, etc.
[0056] 3.3 The experimental results are shown in Table 3: Table 3 is the antibacterial rate-culture time comparison experimental data Group Material formula Escherichia coli inhibition rate (%) Staphylococcus aureus inhibition rate (%) Mildew resistance level (0-5 levels, 0 level is optimal) Mold growth after 7 days Experimental group 1 Heat pump special formulation (TiO2 2 parts) 99.6 99.4 0 level No mold growth Experimental group 2 VOCs formulation (Ti02 2.5 parts) 99.8 99.7 0 level No mold growth Control group 1 Pure 13X zeolite 12.3 15.7 4 level Surface covered with ≥60% mold Control group 2 Traditional composite material 18.5 22.1 3 level Surface covered with 30%-60% mold From the above data, it can be seen that the antibacterial rate of the experimental group is ≥99.4%, and the mold prevention level reaches the optimal 0 level, while the antibacterial rate of the control group is less than 23% and the mold prevention level is 3-4, which verifies the broad-spectrum antibacterial effect of TiO2 nanoparticles, and solves the problem of microbial growth in high humidity environment. Figure 4 Similarly, the effect is also shown.
[0057] 4. Structural stability verification 4.1 Experimental purpose: verify the improvement of the structural strength and cyclic stability of the gradient carbonization + in-situ coating of the scheme, and compare the embrittlement and capacity attenuation problems of traditional materials.
[0058] 4.2 Experimental design Experimental group: heat pump special formula of the scheme (experimental group 1); Control group: traditional zeolite-carbonized pine (control group 2).
[0059] Experimental conditions: (1) Compressive strength test: a universal testing machine was used, the loading rate was 1 mm / min, the compressive strength of φ5 mm cylindrical samples was measured (n=5, average value was taken); (2) Cyclic stability test: under the conditions of 25°C / 90%RH (adsorption) and 40°C hot air + photocatalysis (regeneration), the adsorption-regeneration cycle was repeated for 50 times, the capacity retention rate and sample integrity (whether broken) after the cycle were measured.
[0060] Execution standard: GB / T 14800-2010.
[0061] 4.3 The experimental results are shown in Table 4: Table 4 is the compressive capacity retention rate comparison experimental data Group Material formula Compressive strength (MPa) Capacity retention rate after 50 cycles (%) Sample state after cycling Experimental group 1 Heat pump special formula 1.8 95.2 No fragmentation, complete surface, no component peeling Control group 2 Traditional composite material 0.7 72.3 About 30% of the sample was fragmented, with components falling off the surface From the above data, the compressive strength of the experimental group is 1.8 MPa, which is 2.6 times that of the control group, and the capacity retention rate after 50 cycles is 95.2%, which is much higher than that of the control group 72.3%, and there is no fragmentation phenomenon, verifying the significant improvement of structural stability.
[0062] 5. Multi-scene adaptation performance verification 5.1 Experimental purpose: Verify the adaptability of different formulations in this scheme to CO2 heat pump, high humidity VOCs, and high salt wastewater 3 scenes, and compare the scene limitations of existing technologies.
[0063] 5.2 Experimental design Experimental group: Scene customized formulation in this scheme 3 Experimental group 1: CO2 heat pump special formula (adapt to heat pump scene); Experimental group 2: High humidity VOCs purification formula (adapt to VOCs scene); Experimental group 3: High salt wastewater formula (adapt to wastewater scene).
[0064] Control group: General existing material Control group 3: Commercial activated carbon (commonly used for VOCs / wastewater treatment, no CO2 selectivity); Control group 4: Commercial zeolite molecular sieve (commonly used for CO2 adsorption, no wastewater / VOCs adaptability).
[0065] Experimental conditions: (1) Heat pump scene: Measure CO2 separation efficiency at -10℃ / 90%RH (simulate heat pump device, gas-liquid mixture flow rate 10 L / min); (2) VOCs scene: Measure toluene removal rate (toluene concentration 500 mg / m 3 , air volume 1 m 3 / h, 25℃ / 90%RH); (3) Wastewater scene: Measure phosphate adsorption capacity (wastewater phosphate concentration 100 mg / L, pH=7, 25℃, adsorption time 24 h).
[0066] 5.3 The experimental results are shown in Table 5: Table 5 is the multi-scene adaptability verification experimental data Group Material formula / type Heat pump scenario: CO2 separation efficiency (%) VOCs scenario: toluene removal rate (%) Wastewater scenario: phosphate adsorption capacity (mg / g) Scenario adaptability evaluation Experimental group 1 Heat pump special formula 98.5 65.2 8.3 Adapt to heat pump (excellent), other scenarios (general) Experimental group 2 High humidity VOCs purification formula 92.3 91.5 10.2 Adapt to VOCs (excellent), other scenarios (good) Experimental group 3 High salt wastewater formula 85.7 72.3 18.5 Adapt to wastewater (excellent), other scenarios (good) Control group 3 Commercial activated carbon 42.1 (no selectivity) 88.3 12.7 Adapt to VOCs (good), heat pump (poor) Control group 4 Commercial zeolite molecular sieve 90.5 45.8 6.2 Adapt to heat pump (good), VOCs / wastewater (poor) From the above data, this scheme can be adjusted by formulation, realizing "one type of formulation adapting to one type of scene (excellent), and considering other scenes (good / general)", while the existing technology material can only adapt to one type of scene. This scheme has obvious advantages in multi-scene adaptation.
[0067] Example 3 This example takes "1 ton per day (continuous production for 24 h, capacity 41.7 kg / h)" as the target scale, uses industrial-grade continuous equipment, and reproduces the special formula for heat pump: 30 parts of directional carbonized pine, 55 parts of 13X zeolite, 3.5 parts of La(NO3)3, 2 parts of TiO2, 1.2 parts of KH-570, 8 parts of silica-alumina sol, and 1 part of Li2CO3. Through multiple batch production verification, the effect of large-scale production is verified, and the laboratory small test data is compared to confirm that the performance does not decay and the cost is controllable.
[0068] 6.1 Batch production effect verification scheme (1) Verification of core indicators Three indicators need to be verified in batch production: Product performance consistency: intra-batch / batch-to-batch deviation of key performance (CO2 adsorption capacity, compressive strength, and antibacterial rate); Production stability: continuous operation of equipment, failure downtime, and yield; Cost and efficiency: unit production cost, hourly capacity, and comparison with laboratory small test data.
[0069] (2) Experimental design and data recording ① Batch setting: three batches of continuous production, each batch production time 8 h, yield about 333 kg / batch, marked as batch batch 1, batch batch 2, batch batch 3, and laboratory small test batch (10 kg, marked as small test control group) as a benchmark for comparison.
[0070] ② Sampling and detection method Sampling frequency: sample every 2 h in each batch, a total of 4 times / batch, sampling amount 500 g / time, mix and measure average performance; Detection items: CO2 adsorption capacity (25℃ / 90%RH, GB / T 39753-2021); Compressive strength (φ5 mm cylindrical sample, GB / T 14800-2010, n=10, average value); Rare earth (La 3+ ) loading (XRF, accuracy ±0.05 wt%); Escherichia coli antibacterial rate (GB / T 21866-2008); Yield (qualified product weight / total raw material input weight x 100%, qualified standard: no cracking in appearance, density 0.9-1.0 g / cm 3 ).
[0071] 6.2 Batch production verification results and analysis (1) Product performance consistency (Table 6) Table 6 is the batch production test performance consistency data Test items Batch batch 1 (n=4) Batch batch 2 (n=4) Batch batch 3 (n=4) Batch-to-batch deviation (%) Small test control group Performance attenuation rate (%) in large-scale production CO2 adsorption capacity (mg / g) 30.5±0.4 30.8±0.3 30.6±0.5 0.98 30.8±0.2 0.65 Compressive strength (MPa) 1.75±0.08 1.82±0.06 1.78±0.07 1.92 1.80±0.05 0.56 La 3+ loading (wt%)]]> 1.82±0.04 1.82±0.03 1.83±0.05 0.82 1.84±0.02 0.54 Escherichia coli inhibition rate (%) 99.5±0.2 99.7±0.1 99.6±0.2 0.20 99.6±0.1 0.10 Production rate (%) 96.8 97.2 96.5 0.36 92.5 (small test manual operation) -(Batch is higher) From the above data, the batch-to-batch deviation of the key performance indicators of the three batches is ≤1.92%, which is much lower than the standard of ≤5% for industrial-grade materials, indicating that the parameter control accuracy of the continuous equipment meets the requirements; the attenuation rate of the CO2 adsorption capacity and the compressive strength of the large-scale production is ≤0.65%, which can be ignored, and there is no performance loss in process scaling; the yield of batch production is 96.5%-97.2%, which is higher than 92.5% of the small test, and the automatic equipment reduces the loss of raw materials caused by manual operation.
[0072] (2) Production stability (Table 7) Table 7 is the production stability results of batch production test Production index Design target Actual achieved value Compliance Continuous operation time ≥24 h 24 h no stop Compliance Fault stop probability ≤1% 0.3% (1 alarm) Compliance Hourly production capacity 41.7 kg / h 42.3 kg / h Exceeds standard Online detection qualified rate ≥95% 98.7% Compliance From the above results, the equipment runs continuously for 24 hours without major failures, with a failure downtime of only 0.3%, indicating that the industrial equipment is well adapted; the hourly capacity exceeds the design target, as the temperature gradient of the extruder die is optimized in batch production, improving the molding efficiency.
[0073] (3) Cost and efficiency comparison (small test vs batch) (Table 8) Table 8 is the comparison data of batch production test and laboratory small test production Cost / efficiency index Laboratory small test (10 kg / batch) Batch production (1 ton per day) Variation range (%) Unit production cost (yuan / kg) 85.6 52.3 -38.9 Unit energy consumption (kW·h / kg) 8.2 4.5 -45.1 Labor cost proportion 35% 12% -65.7 From the above data, the unit cost of batch production is reduced by 38.9% compared to the small test, which is mainly due to the scale effect and automation cost reduction, reaching the industrialization profit threshold (target ≤60 yuan / kg); the unit energy consumption is reduced by 45.1%, as the waste heat recovery system of industrial equipment and continuous production reduces the energy consumption waste of "warming-cooling", meeting the requirements of low-carbon production.
[0074] Example 4 This example shows the trial operation results.
[0075] 7.1 CO2 heat pump system integration application The material of Experiment Group 1 is filled in the core layer of the transcritical CO2 heat pump gas-liquid separation device: Operating conditions: -15℃ to 40℃, relative humidity 60%-95%; Operation effect: system COP (performance coefficient) increased by 18%, defrosting frequency reduced by 70%, annual energy consumption reduced by 22%, and microbial detection rate was 0.
[0076] 7.2 High-humidity VOCs treatment application in chemical park In a VOCs treatment device with a wind volume of 20000 m 3 / h in a certain petrochemical park, the material of Experiment Group 2 is used: Treatment effect: The removal rates of toluene and xylene are 91% and 88% respectively, the outlet concentration meets GB 31571-2015 standard, the regeneration cycle is extended to 7 days, and the annual operation and maintenance cost is reduced by 35%.
Claims
1. A composite adsorbent material for CO2 gas-liquid separation, characterized in that, The raw materials, by weight, include: 20-35 parts of directional carbonized pine wood powder, 45-60 parts of 13X / NaY type zeolite, 2-4 parts of rare earth modifier, 1-3 parts of nano-functional particles, 0.5-2 parts of hydrophobic modifier, 5-10 parts of inorganic binder, and 0.5-1.5 parts of low-temperature sintering aid. The directional carbonized pine wood powder is subjected to gradient carbonization at 500-550 ℃, resulting in a specific surface area ≥400 m². 2 / g, the nanofunctional particles are TiO2 or ZnO, with a particle size of 20-50 nm.
2. The composite adsorbent material according to claim 1, characterized in that: The zeolite is composed of 13X type and NaY type in a weight ratio of (0-1):(1-0).
3. The composite adsorbent material according to claim 1, characterized in that: The rare earth modifier mentioned is one containing La. 3+ ions or Ce 3+ Salt solutions of ions.
4. The composite adsorbent material according to claim 1, characterized in that: The hydrophobic modifier is KH-570, the inorganic binder is a mixture of silica sol and alumina sol in a 1:1 weight ratio, the low-temperature sintering aid is Li2O3, and the sintering temperature is controlled at 250-280 ℃.
5. A method for preparing the composite adsorbent material according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Pine wood powder is acid washed and carbonized at a gradient of 500-550 ℃ to obtain directional carbonized pine wood powder; (2) Zeolite and rare earth modifier were stirred at 65℃ for 3 h, and nano-functional particles were added and ultrasonically dispersed to obtain double-modified zeolite; (3) Mix directional carbonized pine powder, double-modified zeolite, inorganic binder, and low-temperature sintering aid, spray in hydrophobic modifier for in-situ coating, and extrude into shape using a twin-screw extruder; (4) Continuous sintering at 250-280 ℃ to obtain composite adsorbent material.
6. The preparation method according to claim 5, characterized in that: In step (1), the gradient carbonization of pine powder is carried out by continuous heating under a nitrogen atmosphere. The heating stages include holding at 200℃ for 1 h, holding at 400℃ for 1 h, and holding at 550℃ for 1 h. The heating stages are carried out by slowly heating at 5℃ / min.
7. The preparation method according to claim 5, characterized in that: In step (2), the zeolite and rare earth modifier solution are mixed at a solid-liquid ratio of 1:
8.
8. A method for applying the composite adsorbent material as described in any one of claims 1-4, characterized in that, include: (1) Adjust the formula according to the application scenario: add 1-1.2 parts by weight of hydrophobic modifier for heat pump scenario, and remove hydrophobic modifier for water treatment scenario; (2) When the adsorption capacity drops to 80% of the initial value, the composite adsorption material is regenerated.
9. The application method according to claim 8, characterized in that: The regeneration includes: (1) Photocatalysis: First, ultraviolet light is activated, and the adsorbed organic pollutants are decomposed by the photocatalytic effect of TiO2 in the material under ultraviolet light; (2) Low temperature hot air synergy: After the photocatalysis has been running for 20-30 min, the hot air is turned on simultaneously. The hot air is 40℃ and the wind speed is 0.5-1 m / s to help desorb the physically adsorbed CO2 and water vapor. (3) Regeneration termination: When the CO2 concentration in the exhaust gas decreases to the ambient concentration, turn off the ultraviolet light, and turn off the hot air 10 minutes later. The adsorption capacity of the material will recover to more than 95% of the initial value.
Citation Information
Patent Citations
Zeolite-biomass carbon adsorbent as well as preparation method and application thereof
CN117101603A